Anti-radiation erbium-ytterbium co-doped optical fiber core rod, preform, optical fiber and preparation method thereof

By doping rare earth oxides and high hydroxy quartz casings in erbium ytterbium co-doped optical fibers, the problem of difficult to take into account both radiation resistance and pumping light efficiency in the prior art is solved, and efficient radiation resistance and signal gain are achieved. Suitable for spatial communication.

CN119241082APending Publication Date: 2025-01-03YANGTZE OPTICAL FIBRE & CABLE CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411383405.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing erbium-ytterbium co-doped optical fibers are difficult to take into account both the radiation resistance and the pump light absorption efficiency under irradiation conditions, and the introduction of heavy metal ions will lead to an increase in attenuation and affect the signal gain.

Method used

Using radiation-resistant double-clad erbium-ytterbium co-doped optical fiber, the core and step layers are doped with rare earth oxides Ce2O3 and/or Nb2O3, and the electron and hole defects induced by radiation are directly absorbed through the valence change of rare earth ions, and The radiation resistance is improved through the step layer to absorb the radiation in advance, and the combination of high hydroxyl and F-doped quartz casing.

Benefits of technology

It significantly improves the radiation resistance of optical fibers, maintains high pump light absorption efficiency and conversion efficiency, avoids the problem of attenuation caused by heavy metal ions, and is suitable for communication applications in radiation environments such as space.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241082A_ABST
    Figure CN119241082A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of active optical fibers, and particularly relates to an anti-radiation erbium-ytterbium co-doped optical fiber core rod, a preform, an optical fiber and a preparation method thereof. The rare earth doped core rod of the anti-radiation erbium-ytterbium co-doped optical fiber provided by the invention comprises a rare earth doped fiber core and a step layer wrapping the fiber core, and the step layer contains a rare earth co-doped substance Ce2O3 and / or Nb2O5 besides a substrate SiO2 and co-doped substances GeO2 and P2O5. The variable-valence rare earth co-doped substance is doped in the step layer, part of rays are absorbed in advance in the Ce < 4 + > / Ce < 3 + > and / or Nb < 5 + > / Nb < 3 + > variable-valence balance process, the anti-radiation performance of the step layer is improved, part of rays are isolated in advance through the step layer to protect the fiber core, and then the overall anti-radiation performance of the optical fiber is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of active optical fibers, and more specifically, relates to a radiation-resistant erbium-ytterbium co-doped optical fiber core rod, a preform rod, an optical fiber and a preparation method thereof. Background Art

[0002] Optical fiber communication is one of the advantageous solutions for satellite Internet, and to achieve long-distance optical fiber communication, it is necessary to use optical fiber amplifiers to amplify the transmission signal to compensate for the signal attenuation during the transmission process. Erbium-ytterbium co-doped optical fiber is an important gain medium for optical fiber amplifiers, but traditional erbium-ytterbium co-doped optical fiber is highly sensitive to radiation. After being irradiated, the attenuation of the optical fiber will increase sharply, resulting in a decrease in signal gain.

[0003] In order to ensure the single-mode output of Er-Yb co-doped optical fiber, it is necessary to design a Ge and P co-doped step layer on the outer layer of the fiber core. 2 , P 2 O 5 Sensitive to irradiation, the absorption efficiency of the cladding structure to the cladding pump light will be reduced to a certain extent under irradiation conditions. Therefore, some existing technologies also propose to introduce heavy metal ions such as Ce, Pd, and Ti into the cladding and coating of the optical fiber to improve the overall radiation resistance of the optical fiber. However, the introduction of heavy metal ions into the core layer and cladding of the optical fiber will sharply increase the attenuation of the optical fiber, especially Pd and Ti ions, which affect the pump light absorption efficiency and conversion efficiency of the Er-Yb co-doped optical fiber. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a radiation-resistant double-clad erbium-ytterbium co-doped optical fiber rare earth doped core rod, optical fiber preform, optical fiber and preparation method thereof, aiming to solve the technical problem that the radiation resistance performance of the prior art double-clad erbium-ytterbium co-doped optical fiber, the pump light absorption efficiency and the conversion efficiency of the optical fiber cannot be taken into account at the same time.

[0005] To achieve the above object, the present invention provides a radiation-resistant double-clad erbium-ytterbium co-doped optical fiber rare earth doped core rod, comprising a rare earth doped core and a step layer wrapping the core; wherein: the step layer contains in addition to the matrix SiO 2 And the co-doped material GeO 2 and P 2 O 5 In addition, it also contains rare earth co-doping material Ce 2 O 3 and / or Nb 2 O 5 .

[0006] As a further improvement of the present invention, the co-doped substances contained in the rare earth-doped core and their molar percentages are respectively:

[0007] Yb 2 O3 : 0.2-1.4 mol%, preferably 1.2-1.3 mol%;

[0008] Er 2 O 3 : 0.02-0.1 mol%, preferably 0.02-0.05 mol%;

[0009] P 2 O 5 :10~13mol%;

[0010] Al 2 O 3 : 0.1-1 mol%, preferably 0.4-0.6 mol%;

[0011] Ce 2 O 3 :0.02~0.5mol%, preferably 0.2~0.4mol%.

[0012] Further preferably, the co-doped substances contained in the rare earth-doped core and their molar percentages are respectively:

[0013] Yb 2 O 3 : 0.2-1.4 mol%, preferably 1.2-1.3 mol%;

[0014] Er 2 O 3 : 0.02-0.1 mol%, preferably 0.02-0.05 mol%;

[0015] P 2 O 5 :10~13mol%;

[0016] Al 2 O 3 : 0.1-1 mol%, preferably 0.4-0.6 mol%;

[0017] Ce 2 O 3 : 0.02-0.5 mol%, preferably 0.2-0.4 mol%;

[0018] Nb 2 O 5 :0.02~0.1mol%, preferably 0.08~0.1mol%.

[0019] As a further improvement of the present invention, the co-doped substances contained in the step layer and their molar percentages are respectively:

[0020] GeO 2: 6 to 10 mol%; preferably 7 to 9 mol%;

[0021] P 2 O 5 : 1 to 4 mol%; preferably 1 to 2 mol%;

[0022] Ce 2 O 3 :0.02~0.5mol%; preferably 0.04~0.06mol%.

[0023] As a further improvement of the present invention, the co-doped substances contained in the step layer and their molar percentages are respectively:

[0024] GeO 2 : 6 to 10 mol%; preferably 7 to 9 mol%;

[0025] P 2 O 5 : 1 to 4 mol%; preferably 1 to 2 mol%;

[0026] Ce 2 O 3 : 0.02-0.5 mol%; preferably 0.04-0.06 mol%;

[0027] Nb 2 O 5 :0.02~0.1mol%, preferably 0.04~0.06mol%.

[0028] Core layer SiO removal 2 External inclusion of co-doping material Er 2 O 3 , Yb 2 O 3 , P 2 O 5 、Al 2 O 3 、Ce 2 O 3 In the preferred embodiment, the co-doping material Nb 2 O 5 , through doping design to ensure that the optical fiber has high pump light absorption efficiency and conversion efficiency. 2 O 3 and Yb 2 O 3 As a gain ion, P 2 O 5 It plays a role in improving the first two in SiO 2 The effect of solubility in Al 2 O 3 and P 2 O5 Co-doping can improve Er 2 O 3 and Yb 2 O 3 The solubility of Ce 2 O 3 By Ce 3+ / 4+ The change in the valence state of the ions plays a role in improving the radiation resistance of the optical fiber. As a further explanation of the above doping components, in the various doping materials in the fiber core, in order to ensure that Yb 2 O 3 and Er 2 O 3 The high solubility of rare earth components in quartz, P 2 O 5 The doping concentration is preferably 10 to 13 mol%, wherein Al 2 O 3 The preferred doping concentration is 0.1-1 mol%, and more preferably 0.4-0.6 mol%. Too high a doping concentration will reduce the Yb 3+ , Er 3+ The energy transfer efficiency between them is reduced. The other doping components are preferably doped at a lower concentration due to the increase in fiber loss. 2 O 3 The preferred concentration is 0.02 to 0.5 mol%, and more preferably 0.04 to 0.06 mol%; Nb 2 O 5 The preferred concentration is 0.02 to 0.1 mol%, and more preferably 0.04 to 0.06 mol%, in order to improve the radiation resistance of the entire optical fiber while ensuring that the optical fiber maintains a low cladding loss.

[0029] According to another aspect of the present invention, an optical fiber preform is provided, comprising the rare earth doped core rod and a high hydroxyl and / or fluorine doped quartz sleeve. The optical fiber preform is prepared by combining the rare earth doped core rod and the quartz sleeve through a tube-rod method.

[0030] As a preferred solution, the hydroxyl content in the quartz sleeve is between 100 and 1000 ppm, more preferably between 400 and 800 ppm; and / or the F doping amount is 0.02 to 0.1 mol%, more preferably between 0.05 and 0.1 mol%.

[0031] According to another aspect of the present invention, a radiation-resistant double-clad Er-Yb co-doped optical fiber is provided, which is produced by drawing the optical fiber preform rod, and then coating the bare optical fiber formed after drawing and curing the coating.

[0032] As a preferred solution, the radiation-resistant double-clad erbium-ytterbium co-doped optical fiber of the present invention comprises a rare earth-doped core, a step layer, a quartz inner cladding, a low-refractive index coating outer cladding and a high-refractive index coating arranged in sequence from the inside to the outside.

[0033] As a further improvement of the present invention, in order to ensure that the signal light is better bounded in the core for transmission, the relative numerical aperture NA of the core and the step layer is 0.07-0.14; in order to ensure that the cladding pump light is better bounded in the inner cladding and fully absorbed, the relative numerical aperture NA of the quartz inner cladding and the low-refractive-index coating outer cladding is ≥0.46.

[0034] As a further improvement of the present invention, the end face of the inner cladding of the quartz is an octagonal structure, and the ratio of the diameter of the step layer to the core is 2.5 to 3.5. When the ratio is less than 2.5, the core light cannot be well confined in the core layer, especially when the optical fiber is bent; when the ratio is greater than 3.5, the cladding pump light is easy to form spiral light in the step layer and reduce the pump efficiency.

[0035] As a preferred solution, the outer shape of the quartz sleeve is polished into an octagonal structure, which corresponds to the octagonal structure of the end face of the optical fiber after the optical fiber is drawn.

[0036] Different from ordinary optical fiber, the pump band and gain band of the double-clad single-mode erbium-ytterbium co-doped optical fiber of the present invention are 900-1000nm and 1530-1565nm respectively. In view of the absorption of 940nm pump light by hydroxyl, it is generally believed that doping hydroxyl into the double-clad single-mode erbium-ytterbium co-doped optical fiber will reduce the conversion efficiency of the optical fiber due to the absorption of pump light, and doping hydroxyl is generally not considered. However, the present invention experimentally found that when hydroxyl is doped into the quartz sleeve (corresponding to the inner quartz cladding), it will not only not lead to a decrease in the conversion efficiency of the optical fiber, but also significantly improve its radiation resistance. Therefore, in the preferred embodiment of the present invention, the quartz sleeve is a high-hydroxyl and / or F-doped quartz sleeve, and its hydroxyl content is preferably between 100 and 1000ppm, more preferably between 400 and 800ppm, and / or, the F doping amount is 0.02 to 0.1mol%, and more preferably 0.05 to 0.1mol%. Since the quartz sleeve and the rare earth doped core rod are combined and prepared by the tube-rod method, the quartz sleeve corresponds to the quartz inner cladding structure of the final optical fiber, so the hydroxyl content in the quartz inner cladding is between 100 and 1000 ppm, and / or the F doping amount is 0.02 to 0.1 mol%. Experiments have found that the quartz sleeve has a low hydroxyl content and cannot enhance the radiation resistance. However, too high a hydroxyl content is indeed likely to increase the overall loss of the optical fiber, affecting the optical fiber transmission and light conversion efficiency. There is also an optimal doping amount range for F doping in radiation-resistant optical fiber. If the doping concentration exceeds a certain level, the radiation resistance of the optical fiber will be reduced. At the same time, too high a F content will reduce the softening temperature of the quartz sleeve and affect the drawing process.

[0037] The inner diameter of the quartz sleeve is slightly larger than the outer diameter of the rare earth doped core rod to avoid scratches between the core rod and the sleeve during the sleeve process, which affects the quality of the drawn optical fiber. The single-side gap between the two is between 0.5 and 1 mm.

[0038] One end of the quartz sleeve is drawn into a cone at high temperature, and the other end is sealed with a vacuum plug after the core rod is inserted.

[0039] The high-hydroxyl quartz sleeve and the F-doped quartz sleeve of the present invention can be customized according to the requirements of the doping amount of hydroxyl and fluorine.

[0040] According to another aspect of the present invention, there is provided a method for preparing the erbium-ytterbium co-doped optical fiber, comprising the following steps:

[0041] S1: mixing raw materials for preparing the step layer uniformly and passing them into a quartz liner tube, and depositing a plurality of step layers on the inner wall of the quartz liner tube at 1600-1700° C. to obtain a quartz liner tube deposited with a plurality of step layers;

[0042] S2: Mix the raw materials for preparing the doped fiber core uniformly and pass them into the quartz liner tube on which the several step layers are deposited in step S1, and deposit several layers of rare earth doped core layers on the inner wall of the quartz liner tube on which the several step layers are deposited at 1450-1650° C. to obtain a quartz tube on which the rare earth doped core layers and step layers are deposited;

[0043] S3: heating the quartz tube on which the rare earth doped core layer and the step layer are deposited in step S2 to 1800-2100° C., and using the surface tension of glass to melt and shrink the quartz tube into a rare earth doped core rod;

[0044] S4: using a tube-rod method to combine a quartz sleeve and the rare earth-doped core rod to form an optical fiber preform rod;

[0045] S5: heating the preform rod to 1900-2100° C. to soften and draw it into an optical fiber, and coating the surface of the optical fiber with a low refractive index coating and a high refractive index outer protective coating in sequence, corresponding to the low refractive index coating outer cladding and the high refractive index coating, respectively; and finally obtaining the radiation-resistant erbium-ytterbium co-doped optical fiber.

[0046] As a further improvement of the present invention, the raw material for preparing the step layer in step S1 includes SiCl 4 , P 2 O 5 ,GeO 2 , and also includes Ce ion chelate and / or Nb ion chelate. The raw material for preparing the doped core in step S2 includes SiCl 4 , P 2 O 5 、AlCl3 , Yb ion chelate, Er ion chelate, Ce ion chelate, and further preferably also includes Nb ion chelate.

[0047] As a further improvement of the present invention, step S1 adopts the gas phase process of MCVD combined with chelate evaporation system (CDS) to convert the reaction raw material SiCl 4 , P 2 O 5 ,GeO 2 Oxygen is loaded into the quartz liner, Ce ion chelate and / or Nb ion chelate are loaded into the quartz liner using helium through the CDS system, the liner is heated to 1600-1700°C to vitrify the raw materials, and several step layers are repeatedly deposited on the inner wall of the quartz tube. The main lamp of the hydrogen-oxygen flame moves at a speed of 100-130 mm / min, preferably 120-130 mm / min, to obtain a suitable core rod size.

[0048] As a further improvement of the present invention, step S2 uses a gas phase process of MCVD combined with a chelate evaporation system (CDS) to convert the reaction raw material SiCl 4 , P 2 O 5 By loading oxygen into the quartz liner, AlCl 3 , Yb ion chelate, Er ion chelate, Ce ion chelate and / or Nb ion chelate are loaded into a quartz liner tube by oxygen or helium, the liner tube is heated to 1450-1650°C to vitrify the raw materials, and several layers of rare earth doped core layers are repeatedly deposited on the inner wall of the quartz tube. The main lamp of the hydrogen-oxygen flame moves at a speed of 100-130 mm / min, preferably 120-130 mm / min.

[0049] The present invention requires that Yb ion chelate, Er ion chelate, Ce ion chelate, and Nb ion chelate be generated into gas and introduced into a quartz glass tube. These ion chelates need to be heated by a device to become gaseous. The heating temperature cannot be greater than 200° C. The saturated vapor pressure is limited so that the amount of the evaporated products of these ion chelates carried out by the carrier gas is saturated. In order to ensure that the doping substance (POCl 3 , Yb ion chelate, Er ion chelate, Ce ion chelate, Nb ion chelate) and doping host (SiCl 4 ) ratio is large enough to achieve high doping, where SiCl 4 The flow rate is limited accordingly.

[0050] As a further improvement of the present invention, in step S5, the preform is heated to 1900-2100° C. to soften and draw into an optical fiber, and a low-refractive index coating and a high-refractive index outer protective coating are sequentially coated on the surface of the optical fiber to obtain a radiation-resistant erbium-ytterbium co-doped optical fiber, wherein the drawing tension is 40-80 g, and the drawing speed is 100-300 mm / min.

[0051] The above-mentioned improved technical features can be combined with each other as long as they do not conflict with each other.

[0052] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0053] (1) To ensure the single-mode output of Er / Yb co-doped optical fiber, a Ge / P co-doped step layer is usually designed on the outer layer of the fiber core. 2 , P 2 O 5 The cladding structure is sensitive to radiation, and the absorption efficiency of the cladding pump light will be reduced under irradiation conditions. To this end, the present invention proposes a rare earth doped core rod of a radiation-resistant erbium-ytterbium co-doped optical fiber, comprising a rare earth doped core and a step layer wrapping the core, and the step layer contains a matrix SiO 2 and co-doped material GeO 2 and P 2 O 5 In addition, it also contains rare earth co-doping material Ce 2 O 3 and / or Nb 2 O 5 The present invention dopes the step layer with a variable valence rare earth co-doping material, and utilizes the variable valence equilibrium process to absorb part of the radiation in advance, which not only improves the radiation resistance of the step layer, but also isolates part of the radiation in advance through the step layer, thus protecting the fiber core and preventing the radiation from irradiating the fiber core to produce defects and affect the 1550nm band signal light transmitted in the fiber core. In addition, Ce in the step layer 2 O 3 and / or Nb 2 O 5 Doping can also avoid the problem of adding heavy metal ions such as Pb and Ti to the cladding in the prior art, which leads to a sharp increase in losses.

[0054] (2) The rare earth doped core rod of the radiation-resistant Er-Yb co-doped optical fiber proposed in the present invention, the core layer and the step layer are both doped with rare earth oxide Ce 2 O 3 and / or Nb 2 O 5 . Ce is used in the fiber core 4+ / Ce 3+ , Nb 5+ / Nb 3+The valence state of the fiber itself changes, directly absorbing the electron and hole defects induced by radiation in the optical fiber, thereby improving the radiation resistance of the optical fiber. At the same time, the rare earth oxide doped in the step layer absorbs part of the radiation in advance to isolate the radiation. The two work together to improve the overall radiation resistance of the optical fiber. The present invention also ensures that the optical fiber has high pump light absorption efficiency and conversion efficiency through doping design.

[0055] (3) In the radiation-resistant erbium-ytterbium co-doped optical fiber preform of the present invention, the quartz sleeve is a high-hydroxyl and / or F-doped quartz tube, and the quartz inner cladding in the radiation-resistant erbium-ytterbium co-doped optical fiber is a high-hydroxyl and / or F-doped inner cladding. Experiments have found that the addition of hydroxyl groups into the optical fiber quartz inner cladding can absorb radiation and reduce SiO 2 The generation of related radiation-induced defects, at the same time, a trace amount of F element is doped in the inner cladding of the optical fiber to replace the O ions in the structure, forming a Si-F bond with stronger bond energy, which also plays a role in reducing SiO 2 The effect of the related radiation-induced defects. Through the doping design of the preform tube, the overall radiation resistance of the erbium-ytterbium co-doped optical fiber of the present invention is further significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 is a schematic diagram of the cross-sectional structure of a radiation-resistant erbium-ytterbium co-doped optical fiber in one embodiment of the present invention;

[0057] Figure 2 A schematic diagram of a typical cross-sectional refractive index curve of a radiation-resistant erbium-ytterbium co-doped optical fiber according to an embodiment;

[0058] Figure 3 It is a pump-output power curve diagram of the comparative example and the embodiment optical fiber before and after irradiation.

[0059] In all the drawings, the same reference numerals are used to represent the same elements or structures, wherein: 1 is the core, 2 is the step layer, 3 is the silica inner cladding, 4 is the low refractive index coating outer cladding, and 5 is the high refractive index protective coating. DETAILED DESCRIPTION

[0060] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0061] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0062] Additionally, references throughout this specification to "one embodiment," "one embodiment," "an example," or similar language indicate that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment of the present invention. Thus, appearances of the phrase "in one embodiment," "in one embodiment," and similar language throughout this specification may, but do not necessarily, all refer to the same embodiment.

[0063] The present invention discloses a radiation-resistant erbium-ytterbium co-doped optical fiber. In some embodiments, Figure 1 As shown, it includes a rare earth doped core 1, a step layer 2, a quartz inner cladding 3, a low refractive index coating outer cladding 4 and a high refractive index protective coating 5 which are arranged in sequence from the inside to the outside. The preparation method thereof includes the following steps: S1, using the gas phase process of MCVD combined with the chelate evaporation system (CDS), first depositing several layers of step layers on the inner wall of the quartz tube; S2, using the above gas phase process, depositing several layers of rare earth doped core layers; S3, heating the quartz tube to 1800-2100°C, so that it is melted and shrunk into a doped quartz rod by tension; S4, using the tube-rod method, combining the high hydroxyl quartz sleeve and the doped quartz rod into an optical fiber preform; S5, heating the preform to 1900-2100°C, softening it and drawing it into an optical fiber, and completing the coating to obtain a radiation-resistant erbium-ytterbium co-doped optical fiber.

[0064] The present invention is based on the gas phase optical fiber preparation technology of MCVD combined with CDS, by introducing rare earth co-doped material Ce into the step layer 2 O 3 and / or Nb 2 O 5 , using the variable valence equilibrium process of rare earth ions to absorb and isolate part of the radiation in advance, thereby improving the radiation resistance of the optical fiber. In a preferred embodiment, by simultaneously introducing variable valence Ce in the step layer and the core layer 3+ / Ce 4+ and / or Nb 3 + / Nb 5+ Ions, Ce is used in the fiber core 4+ / Ce 3+ , Nb 5+ / Nb 3+The valence state of the erbium co-doped fiber changes, directly absorbing the electron and hole defects induced by radiation in the optical fiber, while the rare earth oxide doped in the step layer absorbs part of the radiation in advance and isolates the radiation to protect the core. The two work together to improve the radiation resistance of the erbium-ytterbium co-doped optical fiber, meeting the application in radiation environments such as space. At the same time, in the preferred embodiment of the present invention, a high-hydroxyl and / or F-doped sleeve is used to make a preform rod to draw the optical fiber, and the absorption of hydroxyl groups on radiation ions and the strong Si-F ionic bond are used to further improve the overall radiation resistance of the optical fiber, while ensuring the excellent pump light absorption efficiency and conversion efficiency of the optical fiber.

[0065] The following are specific comparative examples and embodiments:

[0066] Comparative Example 1

[0067] In this comparative example, the core dopant in the Er-Yb co-doped optical fiber comprises P 2 O 5 , Er 2 O 3 , Yb 2 O 3 、Al 2 O 3 and Ce 2 O 3 And the doping concentrations of each dopant are: Yb 2 O 3 1.25 mol%Er 2 O 3 0.04 mol%, P 2 O 5 12.0 mol%Ce 2 O 3 0.3 mol%Al 2 O 3 0.5 mol%. The step layer doping material of the optical fiber comprises P 2 O 5 and GeO 2 , and the doping concentrations of each dopant are P 2 O 5 About 1.0 mol%, GeO 2 About 8 mol%, the rest of the matrix material is SiO 2 .

[0068] The preparation method specifically comprises the following steps:

[0069] S1: The reaction raw material SiCl 4 , P 2 O 5 ,GeO2 Oxygen is loaded into the quartz liner with carrier gas flow rates of 200 sccm, 50 sccm and 500 sccm respectively. The liner is heated to 1650°C to vitrify the raw materials, and several step layers are repeatedly deposited on the inner wall of the quartz tube. The main lamp moves at a speed of 125 mm / min.

[0070] S2: The reaction raw material SiCl 4 , P 2 O 5 Oxygen was loaded into the quartz liner with carrier gas flow rates of 50 sccm, 400 sccm, AlCl 3 , Yb ion chelate, Er ion chelate and Ce ion chelate are loaded into the quartz liner by helium using CDS system, and the carrier gas flow rate is 20sccm, 300sccm, 300sccm and 400sccm respectively. The liner is heated to 1600℃ to make the raw materials vitrify, and several layers of rare earth doped core layer are repeatedly deposited on the inner wall of the quartz tube, and the main lamp moves at a speed of 125mm / min;

[0071] S3: After the core layer is deposited, the quartz tube is heated to 2100°C, and the surface tension of the glass is used to melt and shrink the quartz tube into a rare earth doped core rod;

[0072] S4: using the tube-rod method to select conventional low-hydroxyl (<100ppm) undoped F-quartz tubes to form an optical fiber preform;

[0073] S5: The preform rod is heated to 1950°C to soften and draw into an optical fiber, with a drawing tension of 60g and a drawing speed of 200mm / min. A low-refractive index coating (acrylate with a refractive index of 1.36) and a high-refractive index outer protective coating (acrylic resin with a refractive index of 1.49) are sequentially coated on the surface of the optical fiber to obtain a radiation-resistant erbium-ytterbium co-doped optical fiber.

[0074] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has an optical fiber cladding (edge-to-edge) diameter of 125 μm, a step layer diameter of 25 μm, and a rare earth-doped core diameter of 10 μm.

[0075] Comparative Example 2

[0076] In this comparative example, the core dopant in the Er-Yb co-doped optical fiber comprises P 2 O 5 , Er 2 O 3 , Yb 2 O 3 、Al 2 O 3 and Ce 2 O 3And the doping concentrations of each dopant are: Yb 2 O 3 1.25 mol%Er 2 O 3 0.04 mol%, P 2 O 5 12.0 mol%Ce 2 O 3 0.3 mol%Al 2 O 3 0.5 mol%. The step layer doping material of the optical fiber comprises P 2 O 5 ,GeO 2 and Ce 2 O 3 , and the doping concentrations of each dopant are P 2 O 5 About 1.0 mol%, GeO 2 About 8 mol%, Ce 2 O 3 0.05 mol%, the rest of the matrix material is SiO 2 .

[0077] The preparation method specifically comprises the following steps:

[0078] S1: The reaction raw material SiCl 4 , P 2 O 5 ,GeO 2 Oxygen was loaded into the quartz liner with carrier gas flow rates of 200 sccm, 50 sccm and 500 sccm respectively. Ce ion chelate was loaded into the quartz liner with helium using the CDS system with a carrier gas flow rate of 50 sccm. The liner was heated to 1650°C to vitrify the raw materials, and several step layers were repeatedly deposited on the inner wall of the quartz tube. The main lamp moved at a speed of 125 mm / min.

[0079] S2: The reaction raw material SiCl 4 , P 2 O 5 Oxygen was loaded into the quartz liner with carrier gas flow rates of 50 sccm, 400 sccm, AlCl 3, Yb ion chelate, Er ion chelate and Ce ion chelate are loaded into the quartz liner by helium using CDS system, and the carrier gas flow rate is 20sccm, 300sccm, 300sccm and 400sccm respectively. The liner is heated to 1600℃ to make the raw materials vitrify, and several layers of rare earth doped core layer are repeatedly deposited on the inner wall of the quartz tube, and the main lamp moves at a speed of 125mm / min;

[0080] S3: After the core layer is deposited, the quartz tube is heated to 2100°C, and the surface tension of the glass is used to melt and shrink the quartz tube into a rare earth doped core rod;

[0081] S4: using the tube-rod method to select conventional low-hydroxyl (<100ppm) undoped F-quartz tubes to form an optical fiber preform;

[0082] S5: The preform rod is heated to 1950°C to soften and draw into an optical fiber, with a drawing tension of 60g and a drawing speed of 200mm / min. A low-refractive index coating (acrylate with a refractive index of 1.36) and a high-refractive index outer protective coating (acrylic resin with a refractive index of 1.49) are sequentially coated on the surface of the optical fiber to obtain a radiation-resistant erbium-ytterbium co-doped optical fiber.

[0083] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has an optical fiber cladding (edge-to-edge) diameter of 125 μm, a step layer diameter of 25 μm, and a rare earth-doped core diameter of 10 μm.

[0084] Example 1

[0085] In this embodiment, the core dopant in the radiation-resistant Erbium-Ytterbium co-doped optical fiber comprises P 2 O 5 , Er 2 O 3 , Yb 2 O 3 、Al 2 O 3 and Ce 2 O 3 , and the doping concentrations of each dopant are: Yb 2 O 3 1.25 mol%Er 2 O 3 0.04 mol%, P 2 O 5 12.0 mol%Ce 2 O 3 0.3 mol%Al 2 O 3 0.5 mol%. The step layer doping material of the optical fiber comprises P 2 O 5 ,GeO 2and Ce 2 O 3 , and the doping concentrations of each dopant are P 2 O 5 About 1.0 mol%, GeO 2 About 8 mol%, Ce 2 O 3 0.05 mol%, the rest of the matrix material is SiO 2 .

[0086] The preparation method specifically comprises the following steps:

[0087] S1: The reaction raw material SiCl 4 , P 2 O 5 ,GeO 2 Oxygen was loaded into the quartz liner with carrier gas flow rates of 200 sccm, 50 sccm and 500 sccm respectively. Ce ion chelate was loaded into the quartz liner with helium using the CDS system with a carrier gas flow rate of 50 sccm. The liner was heated to 1650°C to vitrify the raw materials, and several step layers were repeatedly deposited on the inner wall of the quartz tube. The main lamp moved at a speed of 125 mm / min.

[0088] S2: The reaction raw material SiCl 4 , P 2 O 5 Oxygen was loaded into the quartz liner with carrier gas flow rates of 50 sccm, 400 sccm, AlCl 3 , Yb ion chelate, Er ion chelate and Ce ion chelate are loaded into the quartz liner by helium using CDS system, and the carrier gas flow rate is 20sccm, 300sccm, 300sccm and 400sccm respectively. The liner is heated to 1600℃ to make the raw materials vitrify, and several layers of rare earth doped core layer are repeatedly deposited on the inner wall of the quartz tube, and the main lamp moves at a speed of 125mm / min;

[0089] S3: After the core layer is deposited, the quartz tube is heated to 2100°C, and the surface tension of the glass is used to melt and shrink the quartz tube into a rare earth doped core rod;

[0090] S4: Using the tube-rod method, a high OH content (400 ppm) undoped F quartz tube and a doped quartz rod are combined into an optical fiber preform;

[0091] S5: The preform rod is heated to 1950°C to soften and draw into an optical fiber, with a drawing tension of 60g and a drawing speed of 200mm / min. A low-refractive index coating (acrylate with a refractive index of 1.36) and a high-refractive index outer protective coating (acrylic resin with a refractive index of 1.49) are sequentially coated on the surface of the optical fiber to obtain a radiation-resistant erbium-ytterbium co-doped optical fiber.

[0092] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has an optical fiber cladding (edge-to-edge) diameter of 125 μm, a step layer diameter of 25 μm, and a rare earth-doped core diameter of 10 μm.

[0093] Example 2

[0094] In this embodiment, the core dopant in the radiation-resistant Erbium-Ytterbium co-doped optical fiber comprises P 2 O 5 , Er 2 O 3 , Yb 2 O 3 、Al 2 O 3 and Ce 2 O 3 And the doping concentrations of each dopant are: Yb 2 O 3 1.25 mol%Er 2 O 3 0.04 mol%, P 2 O 5 12.0 mol%Ce 2 O 3 0.3 mol%Al 2 O 3 0.5 mol%. The step layer doping material of the optical fiber comprises P 2 O 5 ,GeO 2 and Ce 2 O 3 , and the doping concentrations of each dopant are P 2 O 5 About 1.0 mol%, GeO 2 About 8 mol%, Ce 2 O 3 0.05 mol%, the rest of the matrix material is SiO 2 .

[0095] The preparation method specifically comprises the following steps:

[0096] S1: The reaction raw material SiCl 4 , P 2O 5 ,GeO 2 Oxygen was loaded into the quartz liner with carrier gas flow rates of 200 sccm, 50 sccm and 500 sccm respectively. Ce ion chelate was loaded into the quartz liner with helium using the CDS system with a carrier gas flow rate of 50 sccm. The liner was heated to 1650°C to vitrify the raw materials, and several step layers were repeatedly deposited on the inner wall of the quartz tube. The main lamp moved at a speed of 125 mm / min.

[0097] S2: The reaction raw material SiCl 4 , P 2 O 5 Oxygen was loaded into the quartz liner with carrier gas flow rates of 50 sccm, 400 sccm, AlCl 3 , Yb ion chelate, Er ion chelate and Ce ion chelate are loaded into the quartz liner by helium using CDS system, and the carrier gas flow rate is 20sccm, 300sccm, 300sccm and 400sccm respectively. The liner is heated to 1650℃ to make the raw materials vitrify, and several layers of rare earth doped core layer are repeatedly deposited on the inner wall of the quartz tube, and the main lamp moves at a speed of 125mm / min;

[0098] S3: After the core layer is deposited, the quartz tube is heated to 2100°C, and the surface tension of the glass is used to melt and shrink the quartz tube into a rare earth doped core rod;

[0099] S4: Using the tube-rod method, a high OH content (800ppm) undoped F quartz tube and a doped quartz rod are combined into an optical fiber preform;

[0100] S5: The preform rod is heated to 1950°C to soften and draw into an optical fiber, with a drawing tension of 60g and a drawing speed of 200mm / min. A low-refractive index coating (acrylate with a refractive index of 1.36) and a high-refractive index outer protective coating (acrylic resin with a refractive index of 1.49) are sequentially coated on the surface of the optical fiber to obtain a radiation-resistant erbium-ytterbium co-doped optical fiber.

[0101] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has an optical fiber cladding (edge-to-edge) diameter of 125 μm, a step layer diameter of 25 μm, and a rare earth-doped core diameter of 10 μm.

[0102] Example 3

[0103] In this embodiment, the core dopant in the radiation-resistant Erbium-Ytterbium co-doped optical fiber comprises P 2 O 5 , Er 2 O 3 , Yb 2 O 3、Al 2 O 3 and Ce 2 O 3 And the doping concentrations of each dopant are: Yb 2 O 3 1.25 mol%Er 2 O 3 0.04 mol%, P 2 O 5 12.0 mol%Ce 2 O 3 0.3 mol%Al 2 O 3 0.5 mol%. The step layer doping material of the optical fiber comprises P 2 O 5 ,GeO 2 and Ce 2 O 3 , and the doping concentrations of each dopant are P 2 O 5 About 1.0 mol%, GeO 2 About 8 mol%, Ce 2 O 3 0.05 mol%, the rest of the matrix material is SiO 2 .

[0104] The preparation method specifically comprises the following steps:

[0105] S1: The reaction raw material SiCl 4 , P 2 O 5 ,GeO 2 Oxygen was loaded into the quartz liner with carrier gas flow rates of 200 sccm, 50 sccm and 500 sccm respectively. Ce ion chelate was loaded into the quartz liner with helium using the CDS system with a carrier gas flow rate of 50 sccm. The liner was heated to 1650°C to vitrify the raw materials, and several step layers were repeatedly deposited on the inner wall of the quartz tube. The main lamp moved at a speed of 125 mm / min.

[0106] S2: The reaction raw material SiCl 4 , P 2 O 5 Oxygen was loaded into the quartz liner with carrier gas flow rates of 50 sccm, 400 sccm, AlCl 3, Yb ion chelate, Er ion chelate and Ce ion chelate are loaded into the quartz liner by helium using CDS system, and the carrier gas flow rate is 20sccm, 300sccm, 300sccm and 400sccm respectively. The liner is heated to 1650℃ to make the raw materials vitrify, and several layers of rare earth doped core layer are repeatedly deposited on the inner wall of the quartz tube, and the main lamp moves at a speed of 125mm / min;

[0107] S3: After the core layer is deposited, the quartz tube is heated to 2100°C, and the surface tension of the glass is used to melt and shrink the quartz tube into a rare earth doped core rod;

[0108] S4: using the tube-rod method to select a quartz tube with a high OH content (800 ppm) and doped with F (0.05 mol%) and a doped quartz rod to form an optical fiber preform;

[0109] S5: The preform rod is heated to 1950°C to soften and draw into an optical fiber, with a drawing tension of 60g and a drawing speed of 200mm / min. A low-refractive index coating (acrylate with a refractive index of 1.36) and a high-refractive index outer protective coating (acrylic resin with a refractive index of 1.49) are sequentially coated on the surface of the optical fiber to obtain a radiation-resistant erbium-ytterbium co-doped optical fiber.

[0110] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has an optical fiber cladding (edge-to-edge) diameter of 125 μm, a step layer diameter of 25 μm, and a rare earth-doped core diameter of 10 μm.

[0111] Example 4

[0112] In this embodiment, the core dopant in the radiation-resistant Erbium-Ytterbium co-doped optical fiber comprises P 2 O 5 , Er 2 O 3 , Yb 2 O 3 、Al 2 O 3 and Ce 2 O 3 And the doping concentrations of each dopant are: Yb 2 O 3 1.25 mol%Er 2 O 3 0.04 mol%, P 2 O 5 12.0 mol%Ce 2 O 3 0.3 mol%Al 2 O 3 0.5 mol%. The step layer doping material of the optical fiber comprises P 2 O 5 ,GeO2 and Ce 2 O 3 , and the doping concentrations of each dopant are P 2 O 5 About 1.0 mol%, GeO 2 About 8 mol%, Ce 2 O 3 0.05 mol%, the rest of the matrix material is SiO 2 .

[0113] The preparation method specifically comprises the following steps:

[0114] S1: The reaction raw material SiCl 4 , P 2 O 5 ,GeO 2 Oxygen was loaded into the quartz liner with carrier gas flow rates of 200 sccm, 50 sccm and 500 sccm respectively. Ce ion chelate was loaded into the quartz liner with helium using the CDS system with a carrier gas flow rate of 50 sccm. The liner was heated to 1650°C to vitrify the raw materials, and several step layers were repeatedly deposited on the inner wall of the quartz tube. The main lamp moved at a speed of 125 mm / min.

[0115] S2: The reaction raw material SiCl 4 , P 2 O 5 Oxygen was loaded into the quartz liner with carrier gas flow rates of 50 sccm, 400 sccm, AlCl 3 , Yb ion chelate, Er ion chelate and Ce ion chelate are loaded into the quartz liner by helium using CDS system, and the carrier gas flow rate is 20sccm, 300sccm, 300sccm and 400sccm respectively. The liner is heated to 1650℃ to make the raw materials vitrify, and several layers of rare earth doped core layer are repeatedly deposited on the inner wall of the quartz tube, and the main lamp moves at a speed of 125mm / min;

[0116] S3: After the core layer is deposited, the quartz tube is heated to 2100°C, and the surface tension of the glass is used to melt and shrink the quartz tube into a rare earth doped core rod;

[0117] S4: using the tube-rod method to select a quartz tube with a high OH content (800 ppm) and doped with F (0.1 mol%) and a doped quartz rod to form an optical fiber preform;

[0118] S5: The preform rod is heated to 1950°C to soften and draw into an optical fiber, with a drawing tension of 60g and a drawing speed of 200mm / min. A low-refractive index coating (acrylate with a refractive index of 1.36) and a high-refractive index outer protective coating (acrylic resin with a refractive index of 1.49) are sequentially coated on the surface of the optical fiber to obtain a radiation-resistant erbium-ytterbium co-doped optical fiber.

[0119] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has an optical fiber cladding (edge-to-edge) diameter of 125 μm, a step layer diameter of 25 μm, and a rare earth-doped core diameter of 10 μm.

[0120] Example 5

[0121] In this embodiment, the core dopant in the radiation-resistant Erbium-Ytterbium co-doped optical fiber comprises P 2 O 5 , Er 2 O 3 , Yb 2 O 3 、Al 2 O 3 、Ce 2 O 3 and Nb 2 O 5 And the doping concentrations of each dopant are: Yb 2 O 3 1.25 mol%Er 2 O 3 0.04 mol%, P 2 O 5 12.0 mol%Ce 2 O 3 0.3 mol%Al 2 O 3 0.5mol%Nb 2 O 5 0.1 mol%. The step layer doping material of the optical fiber comprises P 2 O 5 ,GeO 2 and Ce 2 O 3 , and the doping concentrations of each dopant are P 2 O 5 About 1.0 mol%, GeO 2 About 8 mol%, Ce 2 O 3 0.05 mol%, the rest of the matrix material is SiO 2 .

[0122] The preparation method specifically comprises the following steps:

[0123] S1: The reaction raw material SiCl 4 , P 2 O 5 ,GeO 2 Oxygen was loaded into the quartz liner with carrier gas flow rates of 200 sccm, 50 sccm and 500 sccm respectively. Ce ion chelate was loaded into the quartz liner with helium using the CDS system with a carrier gas flow rate of 50 sccm. The liner was heated to 1650°C to vitrify the raw materials, and several step layers were repeatedly deposited on the inner wall of the quartz tube. The main lamp moved at a speed of 125 mm / min.

[0124] S2: The reaction raw material SiCl 4 , P 2 O 5 Oxygen was loaded into the quartz liner with carrier gas flow rates of 50 sccm, 400 sccm, AlCl 3 Yb ion chelate, Er ion chelate, Ce ion chelate and Nb ion chelate are loaded into the quartz liner by helium using CDS system, and the carrier gas flow rate is 20sccm, 300sccm, 300sccm, 400sccm and 30sccm respectively. The liner is heated to 1650℃ to make the raw materials vitrify, and several layers of rare earth doped core layer are repeatedly deposited on the inner wall of the quartz tube, and the main lamp moves at a speed of 125mm / min;

[0125] S3: After the core layer is deposited, the quartz tube is heated to 2100°C, and the surface tension of the glass is used to melt and shrink the quartz tube into a rare earth doped core rod;

[0126] S4: using the tube-rod method to select a quartz tube with a high OH content (800 ppm) and doped with F (0.1 mol%) and a doped quartz rod to form an optical fiber preform;

[0127] S5: The preform rod is heated to 1950°C to soften and draw into an optical fiber, with a drawing tension of 60g and a drawing speed of 200mm / min. A low-refractive index coating (acrylate with a refractive index of 1.36) and a high-refractive index outer protective coating (acrylic resin with a refractive index of 1.49) are sequentially coated on the surface of the optical fiber to obtain a radiation-resistant erbium-ytterbium co-doped optical fiber.

[0128] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has an optical fiber cladding (edge-to-edge) diameter of 125 μm, a step layer diameter of 25 μm, and a rare earth-doped core diameter of 10 μm.

[0129] Example 6

[0130] In this embodiment, the core dopant in the radiation-resistant Erbium-Ytterbium co-doped optical fiber comprises P 2 O 5 , Er 2 O 3 , Yb 2 O 3 、Al 2 O 3 and Ce 2 O 3 And the doping concentrations of each dopant are: Yb 2 O 3 1.25 mol%Er 2 O 3 0.04 mol%, P 2 O 5 12.0 mol%Ce 2 O 3 0.3 mol%Al 2 O 3 0.5 mol%. The step layer doping material of the optical fiber comprises P 2 O 5 ,GeO 2 、Ce 2 O 3 and Nb 2 O 5 , and the doping concentrations of each dopant are P 2 O 5 About 1.0 mol%, GeO 2 About 8 mol%, Ce 2 O 3 0.05mol%Nb 2 O 5 0.05 mol%, the rest of the matrix material is SiO 2 .

[0131] The preparation method specifically comprises the following steps:

[0132] S1: The reaction raw material SiCl 4 , P 2 O 5 ,GeO 2 Oxygen was loaded into the quartz liner with carrier gas flow rates of 200 sccm, 50 sccm and 500 sccm respectively. Ce ion chelate and Nb ion chelate were loaded into the quartz liner with helium using the CDS system with a carrier gas flow rate of 50 sccm. The liner was heated to 1650°C to vitrify the raw materials, and several step layers were repeatedly deposited on the inner wall of the quartz tube. The main lamp moved at a speed of 125 mm / min.

[0133] S2: The reaction raw material SiCl 4 , P 2 O 5 Oxygen was loaded into the quartz liner with carrier gas flow rates of 50 sccm, 400 sccm, AlCl 3 , Yb ion chelate, Er ion chelate and Ce ion chelate are loaded into the quartz liner by helium using CDS system, and the carrier gas flow rate is 20sccm, 300sccm, 300sccm and 400sccm respectively. The liner is heated to 1650℃ to make the raw materials vitrify, and several layers of rare earth doped core layer are repeatedly deposited on the inner wall of the quartz tube, and the main lamp moves at a speed of 125mm / min;

[0134] S3: After the core layer is deposited, the quartz tube is heated to 2100°C, and the surface tension of the glass is used to melt and shrink the quartz tube into a rare earth doped core rod;

[0135] S4: using the tube-rod method to select a quartz tube with a high OH content (800 ppm) and doped with F (0.1 mol%) and a doped quartz rod to form an optical fiber preform;

[0136] S5: The preform rod is heated to 1950°C to soften and draw into an optical fiber, with a drawing tension of 60g and a drawing speed of 200mm / min. A low-refractive index coating (acrylate with a refractive index of 1.36) and a high-refractive index outer protective coating (acrylic resin with a refractive index of 1.49) are sequentially coated on the surface of the optical fiber to obtain a radiation-resistant erbium-ytterbium co-doped optical fiber.

[0137] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has an optical fiber cladding (edge-to-edge) diameter of 125 μm, a step layer diameter of 25 μm, and a rare earth-doped core diameter of 10 μm.

[0138] Example 7

[0139] In this embodiment, the core dopant in the radiation-resistant Erbium-Ytterbium co-doped optical fiber comprises P 2 O 5 , Er 2 O 3 , Yb 2 O 3 、Al 2 O 3 、Ce 2 O 3 and Nb 2 O 5 , and the doping concentrations of each dopant are: Yb 2 O 3 1.25 mol%Er 2 O3 0.04 mol%, P 2 O 5 12.0 mol%Ce 2 O 3 0.3 mol%Al 2 O 3 0.5mol%Nb 2 O 5 0.1 mol%. The step layer doping material of the optical fiber comprises P 2 O 5 ,GeO 2 、Ce 2 O 3 and Nb 2 O 5 , and the doping concentrations of each dopant are P 2 O 5 About 1.0 mol%, GeO 2 About 8 mol%, Ce 2 O 3 0.05mol%Nb 2 O 5 0.05 mol%, the rest of the matrix material is SiO 2 .

[0140] The preparation method specifically comprises the following steps:

[0141] S1: The reaction raw material SiCl 4 , P 2 O 5 ,GeO 2 Oxygen was loaded into the quartz liner with carrier gas flow rates of 200 sccm, 50 sccm and 500 sccm respectively. Ce ion chelate and Nb ion chelate were loaded into the quartz liner with helium using the CDS system with a carrier gas flow rate of 50 sccm. The liner was heated to 1650°C to vitrify the raw materials, and several step layers were repeatedly deposited on the inner wall of the quartz tube. The main lamp moved at a speed of 125 mm / min.

[0142] S2: The reaction raw material SiCl 4 , P 2 O 5 Oxygen was loaded into the quartz liner with carrier gas flow rates of 50 sccm, 400 sccm, AlCl 3Yb ion chelate, Er ion chelate, Ce ion chelate and Nb ion chelate are loaded into the quartz liner by helium using CDS system, and the carrier gas flow rate is 20sccm, 300sccm, 300sccm, 400sccm and 30sccm respectively. The liner is heated to 1650℃ to make the raw materials vitrify, and several layers of rare earth doped core layer are repeatedly deposited on the inner wall of the quartz tube, and the main lamp moves at a speed of 125mm / min;

[0143] S3: After the core layer is deposited, the quartz tube is heated to 2100°C, and the surface tension of the glass is used to melt and shrink the quartz tube into a rare earth doped core rod;

[0144] S4: using the tube-rod method to select conventional low-hydroxyl (<100ppm) undoped F-quartz tubes to form an optical fiber preform;

[0145] S5: The preform rod is heated to 1950°C to soften and draw into an optical fiber, with a drawing tension of 60g and a drawing speed of 200mm / min. A low-refractive index coating (acrylate with a refractive index of 1.36) and a high-refractive index outer protective coating (acrylic resin with a refractive index of 1.49) are sequentially coated on the surface of the optical fiber to obtain a radiation-resistant erbium-ytterbium co-doped optical fiber.

[0146] The radiation-resistant erbium-ytterbium co-doped optical fiber prepared by the above method has an optical fiber cladding (edge-to-edge) diameter of 125 μm, a step layer diameter of 25 μm, and a rare earth-doped core diameter of 10 μm.

[0147] For the radiation-resistant erbium-ytterbium co-doped optical fibers in specific comparative examples 1 to 2 and embodiments 1 to 7, the doping substances at different locations, the types of materials used, and the radiation-induced gain changes under a total irradiation dose of 100 krad are summarized in Table 1:

[0148] Table 1 Fiber doping conditions and radiation-induced gain change test results of different comparative examples and examples

[0149]

[0150]

[0151] By comparing Comparative Example 2 and Example 2 in Table 1, it can be seen that the sleeve doped with high hydroxyl (800ppm) can reduce the radiation gain change value of the optical fiber from 0.0098dB / krad to 0.0044dB / krad; further doping with F (0.1mol%) as in Example 4 further reduces the radiation gain change value to 0.0032dB / krad; however, when the core or step layer is further doped with Nb 2 O 5When the radiation-induced gain variation value is reduced to 0.0015dB / krad and 0.0011dB / krad, the radiation resistance of the optical fiber is improved by more than 10 times compared with Comparative Examples 1 and 2.

[0152] From the comparison between Example 7 and Comparative Examples 1 and 2, it can be seen that the core and step layer are doped with Ce at the same time. 2 O 3 and Nb 2 O 5 Compared with undoped fiber, it can also significantly reduce the radiation-induced gain variation value, indicating that when the core and step layer are doped with a certain amount of rare earth ions at the same time, the variable-valence rare earth ions in the core directly absorb the electron and hole defects induced by radiation in the optical fiber, while the step layer can also isolate and absorb part of the radiation rays for the core in advance, thereby showing a promoting and synergistic effect in improving the radiation resistance.

[0153] Figure 2 This is a schematic diagram of a typical cross-sectional refractive index curve of the radiation-resistant Erbium-Ytterbium co-doped optical fiber of Example 1. Figure 3 The pump-output power curves of the comparative example and the example optical fiber before and after irradiation are shown in Table 1 and Figure 3 It can be seen that the optical fiber prepared in the embodiment of the present invention not only has excellent radiation resistance, but also has high pump light absorption efficiency and conversion efficiency.

[0154] The radiation-resistant erbium-ytterbium co-doped optical fiber of the present invention improves the radiation resistance of the erbium-ytterbium co-doped optical fiber by optimizing the optical fiber material design, and can ensure that the gain medium such as the erbium-ytterbium co-doped optical fiber has good light amplification performance in an environment full of radiation such as space. It is one of the key materials for realizing space communication and integrated space-ground optical communication, and has great practical value and application prospects in the future satellite Internet field.

[0155] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A radiation-resistant double-clad erbium-ytterbium co-doped optical fiber rare earth doped core rod, characterized in that: It comprises a rare earth doped fiber core and a step layer wrapping the fiber core; wherein: The step layer contains not only the matrix SiO2 and the co-doped materials GeO2 and P2O5, but also the rare earth co-doped materials Ce2O3 and / or Nb2O5.

2. The rare earth doped core rod according to claim 1, characterized in that: The co-doped substances contained in the rare earth doped core and their molar percentages are respectively: Yb2O3: 0.2~1.4mol%; Er2O3: 0.02~0.1mol%; P2O5: 10-13 mol%; Al2O3: 0.1~1mol%; Ce2O3: 0.02~0.5mol%; Preferably, the rare earth-doped core further contains a co-doped material Nb2O5, the molar percentage of which is 0.02-0.1 mol%.

3. The rare earth doped core rod according to claim 1, characterized in that: The co-doped substances contained in the step layer and their molar percentages are: GeO2: 6-10 mol%; P2O5: 1-4 mol%; Ce2O3: 0.02~0.5mol%.

4. The rare earth doped core rod according to claim 1, characterized in that: The co-doped substances contained in the step layer and their molar percentages are: GeO2: 6-10 mol%; P2O5: 1-4 mol%; Ce2O3: 0.02~0.5mol%; Nb2O5: 0.02~0.1mol%.

5. The rare earth doped core rod according to claim 1, characterized in that: The relative numerical aperture NA of the fiber core and the step layer is 0.07 to 0.14; and / or, The diameter ratio of the step layer to the core is 2.5-3.

5.

6. An optical fiber preform, characterized in that: The optical fiber preform comprises the rare earth doped core rod as claimed in any one of claims 1 to 5, and also comprises a high hydroxyl and / or fluorine doped quartz sleeve, wherein the optical fiber preform is prepared by combining the rare earth doped core rod and the quartz sleeve through a tube-rod method.

7. The optical fiber preform according to claim 6, characterized in that: The hydroxyl content in the quartz sleeve is between 100 and 1000 ppm, and / or the F doping amount is 0.02 to 0.1 mol%.

8. A radiation-resistant double-clad erbium-ytterbium co-doped optical fiber, characterized in that: The optical fiber preform as claimed in claim 6 or 7 is drawn, and then a coating is applied to the bare optical fiber formed after drawing and cured.

9. The method for preparing the radiation-resistant double-clad erbium-ytterbium co-doped optical fiber according to claim 8, characterized in that: The steps include: S1: mixing raw materials for preparing the step layer uniformly and passing them into a quartz liner tube, and depositing several step layers on the inner wall of the quartz liner tube at 1600-1700° C. to obtain a quartz liner tube with several step layers deposited thereon; S2: uniformly mix the raw materials for preparing the doped fiber core and pass them into the quartz liner tube on which the several step layers are deposited in step S1, and deposit several layers of rare earth doped core layers on the inner wall of the quartz liner tube on which the several step layers are deposited at 1450-1650° C. to obtain a quartz tube on which the rare earth doped core layers and step layers are deposited; S3: heating the quartz tube on which the rare earth doped core layer and the step layer are deposited in step S2 to 1800-2100° C., and using the surface tension of glass to melt and shrink the quartz tube into the rare earth doped core rod; S4: using a tube-rod method to combine the quartz sleeve and the rare earth-doped core rod to form the optical fiber preform rod; S5: heating the optical fiber preform to 1900-2100° C. to soften and draw it into an optical fiber, coating the surface of the optical fiber with a low refractive index coating and a high refractive index outer protective coating in sequence, and obtaining the radiation-resistant erbium-ytterbium co-doped optical fiber after curing.

10. The preparation method according to claim 9, characterized in that: The raw materials for preparing the step layer in step S1 include SiCl4, P2O5, GeO2, and Ce ion chelate and / or Nb ion chelate; and / or, The raw materials for preparing the doped core in step S2 include SiCl4, P2O5, AlCl3, Yb ion chelate, Er ion chelate, Ce ion chelate, and preferably also include Nb ion chelate.

Citation Information

Cited By

  • Polarization-maintaining anti-radiation erbium-ytterbium co-doped optical fiber and preparation method thereof

    CN120630381A

  • A polarization maintaining radiation resistant erbium and ytterbium co-doped optical fiber and a preparation method thereof

    CN120630381B

  • Radiation-resistant erbium-ytterbium co-doped silica fiber with high laser performance and preparation method thereof

    CN120810362A